THE TRADITIONAL VS. THE COST ACCOUNTING CONCEPT OF COST. - Benninger, L. J. (The Accounting Review, 1949)
Abstract The conventional accountant's attitude toward imputed costs emphasizes his tendency to adopt a disbursements or outlay concept of cost. The traditional accountant would claim, for example, that imputed interest as a cost is purely hypothetical and arbitrary. If investment on owned capital is subdivided between those portions invested in machinery and equipment and inventories as contrasted to an investment in land, the traditional accountant would, furthermore, be unwilling to recognize implicit rent. Finally, he does not consistently recommend the inclusion of a charge among the operating accounts for proprietor's salary. Thus the emphasis of traditional accounting revolves about sums of money paid out for goods and services in the accumulation of costs. The cost accounting concept of cost represents a development from period costing to the matching of costs to products. This concept is today still in process of evolution. It does not reject the period concept of cost; rather, it seeks to modify such a concept in order to associate costs with product. It further extends the recognition that period accounting gave to the idea of a going concern.